Taxes. (24th December 2020) - Fama, Eugene F.
Abstract: This is a compendium of notes on taxes. Section 2 presents a general tax scheme. It is a tax on value added by labour and capital that does not favour one or the other. Section 3 contrasts taxation of business income for pass‐through entities and corporations. Section 4 discusses property taxes as taxes on housing services and so a form of income tax. Section 5 turns to wealth taxes. The closing Section 6 attempts to explain why people donate to nonprofits but minimise tax payments to governments, even though governments and nonprofits engage in many of the same activities.